A preventive intervention to modify depression risk targets after breast cancer diagnosis: Design and single‐arm pilot study. Issue 4 (15th March 2019) - Weihs, Karen L.; McConnell, Mairead H.; Wiley, Joshua F.; Crespi, Catherine M.; Sauer‐Zavala, Shannon; Stanton, Annette L.
Abstract: Objective: Apply the National Institutes of Health (NIH) Stage Model to design and test an intervention to prevent depression in breast cancer patients at risk for depression. Methods: We identified mindful emotion awareness, along with approach and avoidance strategies for cancer‐related coping and emotion regulation, as targets for a preventive intervention adapted from the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders. Patients' preferences for individual, in‐person, and time‐efficient sessions informed the design. Patients at risk for depression received a 6‐week, 5‐hour intervention with daily exercises. Intervention targets were assessed at baseline, before each session, and 4‐weeks post intervention. Mixed effects analysis of variance (ANOVA) assessed change over the follow‐up period, controlling for age, partnered status, and disease stage. Results: Fifty‐five percent (40/72) of women screened within 6 months of diagnosis had elevated depression risk. Of these, 24 (60%) signed consent. Sixteen received intervention after five were excluded for current depressive disorder, cognitive impairment, or death. Three dropped out. Ninety‐eight percent attendance and 77% practice days indicated feasibility. Effect sizes (Cohen's d ) corrected for regression to the mean (RTM) were 0.82 for cancer‐related acceptance coping, 0.65 for cancer‐related emotional expression, and 0.32 and 0.42 for decreased cancer‐related avoidance coping and depressive symptoms, respectively. Effect sizes for variables lacking data to correct for RTM were 1.0, 0.7, and 0.5 for decreased rumination, experiential avoidance, and fear of depression, respectively, and 1.3, 0.6, and 0.4 for increased cognitive flexibility, distress tolerance, and describing/not judging emotions, respectively. Conclusions: The feasibility of this intervention and malleability of its targets support its further investigation.